2019
DOI: 10.1002/mp.13453
|View full text |Cite
|
Sign up to set email alerts
|

Robust CT ventilation from the integral formulation of the Jacobian

Abstract: Computed tomography (CT) derived ventilation algorithms estimate the apparent voxel volume changes within an inhale/exhale CT image pair. Transformation-based methods compute these estimates solely from the spatial transformation acquired by applying a deformable image registration (DIR) algorithm to the image pair. However, approaches based on finite difference approximations of the transformation’s Jacobian have been shown to be numerically unstable. As a result, transformation-based CT ventilation is poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 39 publications
0
51
0
Order By: Relevance
“…In another work, Kipritidis et al 20 propose to calculate ventilation by a direct scaling of the HU values, bypassing the need for a DIR solution. Castillo et al 22 have proposed an alternative to the Jacobian-based approach using a mass conserving point cloud density function. Neural networks have also been proposed as a means of generating ventilation images.…”
Section: Calculation Methodologies Of Ct-based Ventilation Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Kipritidis et al 20 propose to calculate ventilation by a direct scaling of the HU values, bypassing the need for a DIR solution. Castillo et al 22 have proposed an alternative to the Jacobian-based approach using a mass conserving point cloud density function. Neural networks have also been proposed as a means of generating ventilation images.…”
Section: Calculation Methodologies Of Ct-based Ventilation Imagingmentioning
confidence: 99%
“…Studies are underway to address the challenges of calculating ventilation information from 4D CBCT images. 22,52 In terms of treatment planning, researchers are employing knowledge-based treatment planning approaches to potentially improve the quality of functional avoidance radiotherapy plans. 67 CT-ventilation based functional avoidance is also being explored retrospectively for use in thoracic proton radiotherapy.…”
Section: Future Work and Summarymentioning
confidence: 99%
“…This property was derived and demonstrated numerically in our previous studies. 10,11 Considering the correlations reported in Table I, robust ventilation algorithms provide a numerical framework that (a) is reproducible with respect to image processing pipeline and (b) generates results consistent with SPECT ventilation. However, the framework does not guard against 4DCT acquisition artifacts, which can lead to substantial differences between DIR solutions generated from competing methods.…”
Section: Resultsmentioning
confidence: 98%
“…As previously described in detail, the uncertainties in the Eqs. () and () measurements can be characterized using the standard errors of the corresponding sample means 10,11 . For IJF, it was shown that with 95% probability||vol)(ϕ)(Ω0.277778em0.277778emHHτ,HH,where the minimum hit count, H, depends on M and τ is a specified tolerance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation